Pengaruh Kebijakan Dividen dan Struktur Modal Terhadap Nilai Perusahaan Manufaktur di Bursa Efek Indonesia - Mangkona, Suriyanti; Fadhilah, Nur; Nurfan, Hayah Masrurah (Amsir Management Journal, 2023)
The study aims to determine the effect of dividend policy and capital structure on firm value of manufacturing companies period 2014-2018. The independent variables used in this study are the dividend policy (dividend payout ratio) and capital structure (debt to equity ratio). The dependent variable used in this study is firm value (price to book value). This research is a quantitative research. The population in this study are all manufacturing companies listed on the indonesia stock exchange period 2014 to 2018 amounting to 162 companies. The selection of the sample using purposive sampling, with some predetermined criteria, the number of samples is 10 manufacturing companies. This data is in the form of financial reports that have been published on the Indonesian stock exchange website. Data analysis techniques used in this study is multiple linear regession analysis. Based on the results of data analysis, it shows that the dividend policy and capital structure have an effect on positively and significant to firm value.